2019
DOI: 10.1108/ilt-07-2018-0296
|View full text |Cite
|
Sign up to set email alerts
|

Life calculation of angular contact ball bearings for industrial robot RV reducer

Abstract: Purpose The purpose of this paper is to analyze the force and basic rating life of angular contact ball bearings of RV reducer under the actual operating condition. Design/methodology/approach Force analysis of angular contact ball bearing under the actual operating condition, calculate the axial, radial load and internal load distribution, calculate the basic rating life of angular contact ball bearing under variable load conditions. Findings The external load has a great influence on the radial load of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…erefore, the performance detection of reducers considerably influences the development of robots and the entire manufacturing industry [4][5][6]. e performance parameters of the reducer generally include the no-load friction torque, torsional stiffness, and transmission efficiency [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the performance detection of reducers considerably influences the development of robots and the entire manufacturing industry [4][5][6]. e performance parameters of the reducer generally include the no-load friction torque, torsional stiffness, and transmission efficiency [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Their results revealed that the modified model, based on contact force curves, could improve the transmission performance of the RV reducer as the load increased. Deng et al [ 7 ] calculated the rated life of the RV reducer’s angular contact ball bearing. They also discovered that bearing life had a significant impact on the total life of the RV reducer under heavy load conditions.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, many experts and scholars have carried out a series of studies on the comprehensive performance of the RV reducer, mainly from the RV reducer transmission accuracy, torsional stiffness, and other aspects. [4][5][6][7] Wang et al 8 established an improved cycloidal gear meshing efficiency model by using the numerical analysis method of mixed elastohydrodynamic lubrication. Yang et al 9 proposed an analytical error modeling method for RV reducer's overconstrained structure, and clearly established the relationship between the original error and transmission accuracy.…”
Section: Introductionmentioning
confidence: 99%